A look back: Ongoing dilemmas for rural schools. (December 2021) - Preston, Teresa
The December 1983 Kappan featured the story of Clinch School in Hawkins County, Tennessee, a small rural school with a student body of 161 students in 12 grades. Teresa Preston explains how the story of the community's fight to keep this school open and under local control is illustrative of the dilemmas surrounding rural schools that have been covered in Kappan for a century. Articles have grappled with whether schools should focus on encouraging students to stay in rural communities, how to ensure that schools are large enough to provide adequate programs but small enough to reflect the immediate community, and what role parent and community preferences should play in improvement plans for rural schools .